Forgiveness in “My Brothers” of Matthew 28:10 and Its Significance for the Matthean Climax (28:16-20) - Bronn, William R. (Biblical theology bulletin, 2010)
Matthew climaxes his Gospel (28:16—20) with the risen Lord, among other things, forgiving the Eleven and, subsequently through baptism, all who would come to believe in him, for their sins, (re)establishing fellowship or brotherhood with himself. Matthew signals this intention by Jesus expressing solidarity with his Eleven, referring to them as “my brothers” (28:10). Brothers alludes to the Genesis story of Joseph pardoning his Eleven brothers (45:1—15). This allusion is confirmed by the perfect correspondence between Genesis 45:1—15 and Matthew 28:16—20 in every element of their commissioning forms and material substance.